2022
DOI: 10.3904/kjim.2020.605
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of hydroxychloroquine in osteoarthritis: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background/Aims: Conventional disease-modifying anti-rheumatic drugs have been trialed in osteoarthritis (OA). Hydroxychloroquine (HCQ), which has shown its effectiveness in rheumatoid arthritis, has been trialed for the treatment of OA; however, its efficacy and safety remain unclear. This systematic review and meta-analysis evaluate efficacy and safety of HCQ for the treatment of OA. Methods: MEDLINE, EMBASE, and Cochrane Central were searched from inception through June 2020. Two reviewers independently scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
(148 reference statements)
0
9
0
Order By: Relevance
“…Currently, there is no disease-modifying treatment option available for the management of OA. Consequently, OA imparts a substantial and increasing health burden, with notable implications for individuals and the healthcare systems globally [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no disease-modifying treatment option available for the management of OA. Consequently, OA imparts a substantial and increasing health burden, with notable implications for individuals and the healthcare systems globally [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, in the majority of studies, we found heterogeneous population of patients with OA since did not consider different phenotypes such as imaging or inflammatory markers. Lastly, due to the insufficient data in some trials, SD values were imputed; however, we used the prescribed methods and assumptions [3,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The final assessment is classified as "Low," or "High" risk of bias or can express "Some concerns". (3).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of osteoarthritis (OA) has significantly improved in the last few decades [1][2][3]. Several treatments have been proposed for OA, including methotrexate, hydroxychloroquine, and tumor necrosis factor (TNF) inhibitors, but none are truly effective at alleviating OA symptoms [4][5][6]. Therefore, OA patients often try alternative and non-pharmacological treatments to decrease their pain and functional disability, despite little to no evidence of clinical efficacy [7,8].…”
Section: Introductionmentioning
confidence: 99%